Improved Design Method of Emulsified Asphalt Cold Recycled Mixture - Zhang Chen; Yuanlu Liang; Jin Yang; Tingyi Xu; Lijun Sun (Frontiers in Materials, 2020)
This paper proposes an improved design method for emulsified asphalt cold recycled mixture (EACRM) so as to solve the “secondary compaction” problem in cold recycled asphalt pavement. First, a temperature prediction equation is established based on measured data of cold recycled asphalt pavement. The equation provides the basis for improving the design method. Second, regarding the shortcomings of the current design methods, we introduce material design principles of EACRM and improve existing methods. Splitting strength (15°C) and unconfined compressive strength (60°C) are chosen as the basis of a double index to determine the asphalt emulsion content. Finally, the performance of the asphalt mixture created using the improved design method is compared to that using the current specifications of China. The results of the comparison validate that the proposed design method can effectively avoid early damage to cold recycled asphalt pavement.